The Level of Metacognitive Thinking and Wisdom among a Sample of University Students and the Relationship Between Them - Al-Sherideh, Mohammad (Jordan Journal of Educational Sciences, 2015)
This study aimed at investigating the level of metacognitive thinking and wisdom among a sample of university students and the relationship between them. The sample consisted of (301) male and female undergraduate students: (149) females and (152) males from the scientific and humanistic colleges. The Arabic version of (Schraw and Dennison, 1994) scale was used along with the Arabic version of the wisdom scale developed (Brown and Greene, 2006).The results showed that students have a moderate level in both their metacognitive thinking and wisdom on the scale as a whole and on its sub-dimensions. The results of the study also showed a positive relationship between metacogntive thinking and wisdom and their dimensions. The results of the study also showed that it is possible to predict the total degree of wisdom from the total degree of the metacogntive thinking and the organizing knowledge dimension only